Update on metabolism of abemaciclib: In silico, in vitro, and in vivo metabolite identification and characterization using high resolution mass spectrometry. Issue 3 (14th January 2020) - Thakkar, Disha; Kate, Abhijeet S.
Abstract: Abemaciclib was approved by the US Food and Drug Administration in 2015 as an advanced treatment for metastatic breast cancer. Identification and characterization of limited numbers of abemaciclib metabolites have been reported in the literature. Therefore, the current study focused on the investigation of the in vitro and in vivo metabolic fate of abemaciclib using high resolution mass spectrometry. Initially, a vulnerable site of metabolism was predicted by the Xenosite web predictor tool. Later, in vitro metabolites were identified from pooled rat liver microsomes, rat S9 fractions, and human liver microsomes. Finally, in vivo metabolites have been detected in plasma, urine, and feces matrix of male Sprague–Dawley rats. A total of 12 putative metabolites (11 phase I and 1 phase II) of abemaciclib and their metabolic pathways were proposed by considering accurate mass, mass fragmentation pattern, nitrogen rule, and ring double bonds of the detected metabolites. Abemaciclib was metabolized via hydroxylation, N ‐oxidation, N ‐dealkylation, oxidative deamination followed by reduction and sulfate conjugation. In the human liver microsomes, maximum numbers of metabolites (11 metabolites) were observed, from which M7, M8, M9, and M11 were human specific. Abstract : In total, 12 metabolites of abemaciclib were identified and characterised using high resolution mass spectrometry. M7, M8, M9 and M11 were human specific metabolites of abemaciclib.